Strategi Guru Dalam Mengatasi Kesulitan Dalam Mengimplemetasikan Pembelajaran di Era Kurikulum Merdeka - A, Aufa; Rangkuti, Luthfiyah Hayati; Harahap, Army Fahita; Azahra, Bella; Alfitriyani, Nuri; Djuhaidi, M. Dzaky Labib (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In the last year, the change from the K13 curriculum to the Merdeka curriculum has been a long implementation process resulting in many obstacles. Both obstacles to students and obstacles to teachers. Based on this, this research was conducted with the aim of finding out teachers' strategies for dealing with this. The method used is a qualitative method by interviewing one of the sources by asking questions that have been prepared. The results of the interview show that teachers must be ready to face every change in the curriculum by improving their quality so that students' output is also of high quality. As a teacher, you must also learn how to create a pleasant learning atmosphere and create and apply learning media in every teaching material you bring, don't forget to also accompanied by the use of technology as a tool to assist the learning process.